International Validation of the Erasmus Guillain–Barré Syndrome Respiratory Insufficiency Score. Issue 4 (21st February 2022) - Doets, Alex Y.; Walgaard, Christa; Lingsma, Hester F.; Islam, Badrul; Papri, Nowshin; Yamagishi, Yuko; Kusunoki, Susumu; Dimachkie, Mazen M.; Waheed, Waqar; Kolb, Noah; Gorson, Kenneth C.; Jacobs, Bart C.; et al.
Abstract : Objective: This study aimed to validate the Erasmus Guillain–Barré Syndrome Respiratory Insufficiency Score in the International Guillain–Barré Syndrome Outcome Study cohort, and to improve its performance and region‐specificity. Methods: We examined data from the first 1, 500 included patients, aged ≥6 years and not ventilated prior to study entry. Patients with a clinical variant or mild symptoms were also included. Outcome was mechanical ventilation within the first week from study entry. Model performance was assessed regarding the discriminative ability (area under the receiver operating characteristic curve) and the calibration (observed vs predicted probability of mechanical ventilation), in the full cohort and in Europe/North America and Asia separately. We recalibrated the model to improve its performance and region‐specificity. Results: In the group of 1, 023 eligible patients (Europe/North America n = 842, Asia n = 104, other n = 77), 104 (10%) required mechanical ventilation within the first week from study entry. Area under the curve values were ≥0.80 for all validation subgroups. Mean observed proportions of mechanical ventilation were lower than predicted risks: full cohort 10% versus 21%, Europe/North America 9% versus 21%, and Asia 17% versus 23%. After recalibration, predicted risks for the full cohort and Europe/North America corresponded to observed proportions. Interpretation: This prospective, international cohort study validated the Erasmus Guillain–Barré Syndrome Respiratory Insufficiency Score, and showed that the model can be used in the full spectrum of Guillain–Barré syndrome patients. In addition, a more accurate, region‐specific version of the model was developed for patients from Europe/North America. ANN NEUROL 2022;91:521–531